Baerveldt glaucoma implant insertion in the posterior chamber sulcus. Issue 6 (14th February 2007) - Tello, Celso; Espana, Edgar M; Mora, Ricardo; Dorairaj, Syril; Liebmann, Jeffrey M; Ritch, Robert
Abstract : Aim: To report the clinical outcome of a surgical technique for insertion of the silicone tube of a Baerveldt glaucoma implant (BGI) in the posterior chamber sulcus. Methods: Non-comparative, interventional case series. Eight eyes of eight patients, with a follow-up of at least 18 months, who underwent insertion of a BGI with the silicone tube placed in the posterior chamber sulcus between 1998 and 2005 were included. Control of intraocular pressure (IOP), number of pressure-lowering medications, visual acuity and surgical complications were recorded. Results: Eight eyes of eight patients (mean (range) age 76.4 (62–94) years) were included in the study. The IOP was reduced from a preoperative mean (SD) of 28.2 (14.4) to 12.6 (5.8) mm Hg at 18 months. The mean (SD) number of preoperative medications for IOP control was reduced from 2.8 (1.5) to 1.3 (1.5) medications in the same period. No complications were observed during surgery or follow-up. Conclusion: Placement of the silicone tube in the posterior chamber sulcus is a safe and effective alternative technique for IOP control in patients with pseudophakia. Sulcus placement may reduce the likelihood of corneal endothelial loss and avoid the need for pars-plana vitrectomy and posterior segment tube insertion in complicated eyes.